Teachers’ professional development: The case of Lithuania - Dromantiene, Leta; Indrašiene, Valdone; Merfeldaite, Odeta; Prakapas, Romas (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2013)
Lifelong learning paradigm raises higher requirements for a teacher: quality and effectiveness are the two key words defining the general education policy of the EU and the main objectives of the current period. Today teachers are required to be able to work in a multicultural environment, flexibly respond and adapt to changes, individualise and differentiate the content of education, and pursue various social functions (such as vocational counseling, conflict management, mediation etc.). Besides high professional requirements teachers are also required to participate in the continuous/further learning process including formal/nonformal professional development, selfeducation, and studies in state and private vocational training organisations not only within the framework of education but also in other spheres. The following question have been raised in the article: how the process of teachers’ professional development is organised in Lithuania?